Analisis sensitivitas emisi gas metana (CH4) pada sawah dengan metode korelasi rank spearman - Azmi, Khairul; Arif, Chusnul (Departemen Teknik Sipil dan Lingkungan IPB, 2018)
Global warming occurs due to increased concentrations of GHGs in Earth's atmosphere. CH4 gas is one of the GHG which potentially 21 times greater to result global warming than CO2. Emissions of CH4 in rice fields affected by irrigation pattern and micro environmental factors. This research aimed to identify the relationship of micro-environmental factors to CH4 emissions and analyse its sensitivity level. The sensitivity analysis of CH4 gas in this study was done by rank Spearman’s correlation method. The results showed that the irrigation pattern was positively correlated with CH4 emissions. Total flux of CH4 for the stagnant regime was 26.00 ± 3.41 x 103 mg/m2/season, wet regime was 15.33 ± 4.37 x 103 mg/m2/season, and dry regime was 11.80 ± 6.72 x 103 mg/m2/season. The micro-environment parameters that was soil pH, soil moisture, soil electrical conductivity, and water level are positively correlated with flux of CH4, meanwhile soil temperature and soil redox potential are negatively correlated with flux of CH4. Based on the analysis, the most sensitive micro-environmental parameters for CH4 gas emissions are soil moisture, with an average rs value is 0.51 and an average R2 is 0.28. Keywords: GHG, methane, sensitivity analysis, Spearman’s correlation, SRI